2007
DOI: 10.1603/0022-0493(2007)100[1871:paioco]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Inheritance of Costs of Resistance to Imidacloprid in Colorado Potato Beetle

Abstract: Reduced fitness among resistant versus susceptible individuals slows resistance evolution and makes it easier to manage. A loss of resistance costs could indicate novel adaptations or mutations contributing to resistance. We measured costs of resistance to imidacloprid in a Massachusetts resistant population compared with a Massachusetts susceptible population in 1999 in terms of fecundity, hatching success, egg development time, and sprint speed. Resistance was additive and seemed to be polygenic with high he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…Over a period of 5 years, the authors observed a considerable increase in the number of growers reporting loss of efficacy of neonicotinoids. Other studies conducted in intensive potato production areas of the East Coast and Midwest have reported similar losses in levels of control associated with the use of the systemic neonicotinoids …”
Section: Discussionmentioning
confidence: 63%
“…Over a period of 5 years, the authors observed a considerable increase in the number of growers reporting loss of efficacy of neonicotinoids. Other studies conducted in intensive potato production areas of the East Coast and Midwest have reported similar losses in levels of control associated with the use of the systemic neonicotinoids …”
Section: Discussionmentioning
confidence: 63%
“…Future studies should investigate the importance of spatial and temporal variation in management practices and land cover types to the maintenance of genetic variation among L. decemlineata populations: careful rotation of insecticide modes of action by certain growers, combined with any potential effect of fitness costs associated with resistance to certain chemicals (Alyokhin & Ferro, ; Baker et al., ), may be delaying evolution of resistance. Landscape connectivity may also affect resistance evolution by increasing the strength of genetic drift relative to selection: landscapes with a lower proportion of potato are expected to have lower patch connectivity for L. decemlineata due to greater distances in space and time between rotated potato fields.…”
Section: Discussionmentioning
confidence: 99%
“…Although relative fitness of resistant Colorado potato beetles is often reduced in comparison with susceptible beetles, their mating behavior is likely to ensure high heterozygocity of the offspring. If inheritance of fitness costs is recessive, as has been demonstrated for at least some Colorado potato beetle populations, this is likely to slow down decline in the frequency of resistant alleles in the absence of selection. Furthermore, when resistance is based on preadaptations like utilizing the toxic host plants, resistant genes might be already present in the population, and the costs associated with the resistance might not always be significant .…”
Section: Colorado Potato Beetle As An Archetype For Resistance Develomentioning
confidence: 96%